Cortical bone laminar analysis reveals increased midcortical and periosteal porosity in type 2 diabetic postmenopausal women with history of fragility fractures compared to fracture-free diabetics. Issue 9 (September 2016) - Heilmeier, U.; Cheng, K.; Pasco, C.; Parrish, R.; Nirody, J.; Patsch, J.; Zhang, C.; Joseph, G.; Burghardt, A.; Schwartz, A.; Link, T.; Kazakia, G.
Abstract Summary We investigated the characteristics and spatial distribution of cortical bone pores in postmenopausal women with type 2 diabetes (T2D). High porosity in the midcortical and periosteal layers in T2D subjects with fragility fractures suggests that these cortical zones might be particularly susceptible to T2D-induced toxicity and may reflect cortical microangiopathy. Introduction Elevated cortical porosity is regarded as one of the main contributors to the high skeletal fragility in T2D. However, to date, it remains unclear if diabetic cortical porosity results from vascular cortical changes or from an expansion in bone marrow space. Here, we used a novel cortical laminar analysis technique to investigate the characteristics and spatial radial distribution of cortical pores in a T2D group with prior history of fragility fractures (DMFx, assigned high-risk group) and a fracture-free T2D group (DM, assigned low-risk group) and to compare their results to non-diabetic controls with (Fx) and without fragility fractures (Co). Methods Eighty postmenopausal women (n = 20/group) underwent high-resolution peripheral quantitative computed tomography (HR-pQCT) of the distal tibia and radius. Cortical bone was divided into three layers of equal width including an endosteal, midcortical, and periosteal layer. Within each layer, total pore area (TPA), total pore number (TPN), and average pore area (APA) were calculated. Statistical analysis employed Mann-Whitney tests and ANOVA with post hoc tests. Results Compared to the DM group, DMFx subjects exhibited +90 to +365 % elevated global porosity (p = 0.001). Cortical laminar analysis revealed that this increased porosity was for both skeletal sites confined to the midcortical layer, followed by the periosteal layer (midcortical +1327 % TPA, p ≤ 0.001, periosteal +634 % TPA, p = 0.002), and was associated in both layers and skeletal sites with high TPN (+430 % TPN, p < 0.001) and high APA (+71.5 % APA, p < 0.001). Conclusion High porosity in the midcortical and periosteal layers in the high-risk T2D group suggests that these cortical zones might be particularly susceptible to T2D-induced toxicity and may reflect cortical microangiopathy.